SWEAR WORDS USED BY JOHN BENETT IN TED 2 MOVIE SCRIPT - Sarmi, Ni Nyoman; Putra, Panji Dewa Sukamto (Faculty of Letters, Dr. Soetomo University, 2017)
The thesis writer focuses on the analysis swear words used by John Bennett in Ted 2 movie script. The objectives of the study are, to find out the types of swear word used by john Bennett in Ted 2I movie script, andÂ the reasons of John Bennett using swear words in Ted 2 movie script. The thesis writer applies the theory Liedlich (1973) to find the types of Swearing and applies the theory of Neel Burton (2012) to find The Reasons of Swearing and the thesis writer also applies a qualitative research.Key Word: Swear Words, Ted 2 Movie scriptÂ